Pengaruh Dosis Bokashi dan Pupuk NPK Terhadap Pertumbuhan dan Hasil Pada Tanaman Kangkung Darat (Ipomoea reptans Poir) - Apandi, Yudi; Mulya, Agus Surya; Mulyana, Hudaya (SINTA Journal (Science, Technology, and Agricultural), 2022)
Experimental research aimed at identifying and studying the interaction between the effects of bokashi and NPK fertilizer doses on the growth and yield of kangkung plants. The research was conducted in Sukahurip Village, Cijambe District, Subang Regency. The altitude of the place is 134 meters above sea level with the soil order Andosol and rainfall type B (wet) based on Schmidt and Ferguson's calculations. The research was conducted for three months, from August to October 2022. Randomized block design (RBD) factorial pattern which consisted of two factors, namely the first factor consisting of 4 levels in the form of bokashi doses of 0 tons ha-1 (b0), 15 tons ha-1 (b1), 30 tons ha-1 (b2) and 40 tons ha-1 (b3). and the second factor in the form of NPK fertilizer consisting of 4 levels, namely: 0 kg ha-1 (n0), 100 kg ha-1 (n1), 200 kg ha-1 (n2) and 300 kg ha-1 (n3) repeated 3 times. The results of the research on the effect of doses of bokashi and NPK fertilizers showed an interaction effect on plant height observations at 14 DAP, 21 DAP and 28 DAP, root removal ratio, fresh weight per plant, fresh weight per plot and dry weight per plant, while the number of leaves observed was not indicating an interaction.